Fighting Two Infection Diseases: The Tales of Local Meat Vendors in dealing with COVID-19 and ASF - CAMEROS, John Paul; TUDY, Randy A.; QUIDET, Ernesto A.; TUDY, Ida G. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
The COVID-19 Pandemic has practically affected businesses all over the world, whether they are small, medium, or macro enterprises. The business community was in survival mode and attempting to recover. In addition to the interruptions caused by the pandemic, the African Swine Fever (ASF) struck numerous nations. The goal of this paper is to look into the experiences of local meat vendors as they dealt with the ASF outbreak and the COVID-19 pandemic. This qualitative phenomenological research involved ten pork meat vendors in the Southern Philippines who participated in the key informant interviews (KII). The data from the interview analysis is used to achieve what is called phenomenological psychological reduction. Ethical concerns, such as maintaining confidentiality and anonymity, were taken into account. Pseudonyms replace the original names to maintain anonymity in this work. Before conducting the interview, the informants read the full content of the informed consent before signing it. Participants were also allowed to use the language they felt comfortable with. This investigation uncovered the following major themes relating to local meat vendors: a huge reduction in income; dealing with government regulations; fear of viruses; and the threat of competition. Two themes emerged for their coping strategies: innovation and strengthening customer loyalty. This study also found that it was difficult for the local meat vendors to cope with the two contagious illnesses (COVID-19 and ASF), but they had to do so to survive and make a livelihood.